IMPLEMENTASI PENGGUNAAN MEDIA GAMBAR DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS IV MATA PELAJARAN IPA DI MI SULAIMANIYAH MOJOAGUNG JOMBANG - Naila Salsabila; Imam Muslih (JOURNAL SAINS STUDENT RESEARCH, 2024)
One element of strategy implementation is learning media which is a means of interaction between teachers and students so that learning activities are more effective and efficient. Media can display information through sound, images, movement and color, both naturally and manipulated. With media, learning goals will be more easily achieved optimally with minimal time and energy. The development of science and technology increasingly encourages reform efforts in the use of technological results in the learning process. There are two focuses in this research, namely: (1) Implementation of the use of image media in the learning process for science subjects at MI Sulaimaniyah Mojoagung Jombang (2) Students' interest in learning in science subjects at MI Sulaimaniyah Mojoagung Jombang Qualitative research approach, type of research is case study. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, drawing conclusions and verification. Meanwhile, the data validity checking technique uses source triangulation and technical triangulation. The results of research regarding the implementation of the use of image media in increasing interest in learning for fourth grade students in science subjects at MI Sulaimaniyah Mojoagung Jombang, the use of image media in the learning process at MI Sulaimaniyah Mojoagung Jombang is optimal based on the results of research that has been carried out and supported by interviews by teachers and students who have also been carried out by researchers, there are many results that support that the use of image media in the learning process is very useful and very interesting. As for the fourthgrade students' interest in learning at MI Sulaimaniyah Mojoagung Jombang, especially in science subjects, the researcher concluded that the students' interest in learning was very visible and was quite evident when carrying out learning activities in class, when paying attention to the teacher explaining, when understanding the use of image media presented by teachers, support from several teacher and student interviews.